Perancangan Decision Support System Dengan Metode TOPSIS Untuk Pemilihan Bahan Baku Pada Perusahaan Manufaktur - Rusito Rusito (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
The development of information system technology has penetrated the decision support system. Decision support systems can be applied in the selection of raw materials in manufacturing companies. The standard quantity of raw materials is the quantity of raw materials that should be used in the management of a particular product. Determining the standard of raw material quality starts from the application of product specifications, both regarding size, shape, color, characteristics, product processing and quality. Decision Support System (DSS) or Decision Support System (DSS) is a system which is able to provide alternatives in problem solving or can communicate for problems with semi-structured or unstructured conditions. This system is used to assist decision making in semi-structured and unstructured situations, where no one knows for sure how decisions should be made. Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is a concept where the best chosen alternative not only has the shortest distance from the positive ideal solution, but also has the longest distance from the negative ideal solution. This concept is widely used in several MADM (Multi Attribute Decision Making) models to solve practical decision problems. Research development uses the R & D (Research and Development) method which is a research method used to produce certain products and test certain products. In this study, only 6 steps were used. The total score for validation is 28. Based on the above calculation, it can be concluded that the validation results from the experts show a value of 4.0 which is between 3.26 - 4.0 which is classified as a very valid category.